2019
DOI: 10.3889/oamjms.2019.737
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' Perceptions of Patient Safety Culture in Intensive Care Units: A Cross-Sectional Study

Abstract: BACKGROUND: Patient safety culture is a relatively new focus where little is known about its current status in Egypt’s teaching hospitals, mainly intensive care units (ICUs). Therefore, the authors of this study attempted to assess the patient safety culture dimensions from the nurses’ perspective. METHODS: An exploratory cross-sectional study was conducted in two ICUs (pediatric ICU and adult ICU) at the University Hospital over 3 months from October till December 2018. Sixty nurses were interviewed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 18 publications
5
11
3
Order By: Relevance
“…This result is also consistent with that of a previous study (Gurková et al, 2019). Likewise, the result is similar with those of studies in Egypt (Salem et al, 2019) and Indonesia (Imelda & AdikWibowo, 2018). The management support for patient safety also had a positive perception when the actions of hospital management exhibited that patient safety is a topmost priority.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is also consistent with that of a previous study (Gurková et al, 2019). Likewise, the result is similar with those of studies in Egypt (Salem et al, 2019) and Indonesia (Imelda & AdikWibowo, 2018). The management support for patient safety also had a positive perception when the actions of hospital management exhibited that patient safety is a topmost priority.…”
Section: Discussionsupporting
confidence: 91%
“…This safety outcome variable is closely linked with other dimensions, such as nonpunitive response to errors, which showed a fair culture of reporting events and adequate staffing in the ICU. Correspondingly, this result is also inconsistent with those of another study in Egypt, in which the majority of respondents indicated that the items on the dimension of frequency of events reported had the lowest positive scores, as reported by the ICU staff of the study setting (Salem et al, 2019). Most of the participants gave a positive perception for feedback and communication about error.…”
Section: Discussioncontrasting
confidence: 84%
“…The lowest reported score (12.0%) was for "Non-Punitive Response to Errors" composite. This is similar to the scores of 16.0% by Salem et al in 2019 [15], 19.8% by Aboul-Fotouh et al in 2012 [31], 21.0% in Jordanian study in 2015, [28] and 26.8% in a Saudi Arabian study in 2014 [32]. However, higher score (44.0%) was reported in a study in USA hospitals 2010 [25].…”
Section: Discussionsupporting
confidence: 86%
“…The present study revealed a friable PSC in most composites. Positive response percentages to individual items ranged from 2.7% to 79.2% with a mean total of 37.3%.Similarly, Salem M et al in 2019 [15] and El-Shabrawy et al in 2015 [16], reported scores of 39.3% and 40%consecutively. However, studies conducted in year 2017 in Cairo [17] and Iran, [18] showed higher scores (62.0%) and (57.7%) respectively [17,18].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation